Comparative analysis of blast prediction software for far-field shock wave effects behind a blast wall - Chester, Alastair; Hazael, Rachael; Critchley, Richard (Sage, 2025)
This paper investigates a selection of current and emerging software used in the prediction of overpressure generated through the detonation of a high explosive in the far field behind a blast wall. In particular, this paper compares the software Autodyn, blastFoam, ProSAir, Viper::Blast and WALAIR++. These packages are compared by simulating a 100 kg TNT explosive charge at a stand-off distance of 25 m from a complex structure, then reviewing the performance in terms of the overpressure results, speed of each modelling package, the degree of effect from mesh, and domain sizes and ease of use. A live experimental trial representing the simulation was also performed, although it used a similar but different explosive, for a high-level comparison. The live-trial instrumentation design details are reviewed and compared with best practice. The choice of software is found to lead to variations in peak pressure predictions of 28%, specific impulse by 10% and the simulation speed can vary by a factor of up to 1600 for this type of study. This shows that the choice of blast software package can have a significant impact on the accuracy and attainability of blast predictions.
Keywords: simulation; blast testing; computational modelling; high explosives; 40 Engineering; Bioengineering; 4005 Civil engineering; 4016 Materials engineering; 4017 Mechanical engineering